Corpo docente e corpo bebê: um olhar para a produção acadêmica - Santos, Patrícia dos (Universidade do Vale do Rio dos Sinos, 2023)
The present Dissertation aims to map and analyze the discourses being produced in academic publications, between the years 2010 and 2022, regarding the relationship between the bodies of infants and the bodies of the teaching staff working in Early Childhood Education. In this sense, this research traces the conception of the body from antiquity to the contemporary, observing the ruptures and continuities that reveal significant transformations in the ways of thinking about the body in the Western context. Likewise, it also discusses the historical constitution of Early Childhood Education and its relationship with the construction of teaching subjectivities, taking into consideration the relationship between the bodies of infants and the bodies of professionals as a fundamental axis of the discussion. Therefore, this Master's Dissertation proposes a methodology inspired by Foucauldian discourse analysis as a way of looking at such discourses. From this investigation, two dimensions of analysis emerge. The first concerns the intricate concept of the body present in the selected works and the indications of a persistent dichotomy between body and mind, still marking the exhausted bodies of the teachers. In the second dimension of analysis, the concept of care and self-care is problematized in order to think about the body, bringing forth the modes of subjectivation and practices of freedom to consider the possibility of alternative ways of life in relation to teaching with infants. It is understood, therefore, that self-care, based on Foucauldian studies, can radically break with any form of dichotomy, as it will consider that one of the important dimensions of this practice of relating to oneself is precisely the creation of a body, understood as a way of life.
Keywords: Corpo; Docência; Bebês; Educação infantil; Cuidado de si; Body; Teaching; Infants; Early childhood education; Self-care; ACCNPQ::Ciências Humanas::Educação